Simulasi Dinamis pada Kereta Penumpang Stainless Steel New Generation menggunakan Metode Multibody Dynamic System (Politeknik Perkeretaapian Indonesia Madiun, 2022)
Stainless steel passenger coach is the most operated passenger coach in Indonesia. Because it has better facilities, cheap, and offering more operation hour. Stainless steel passenger coach fabricated by PT.Industri Kereta Api (PT.INKA) and always improve and keep innovate from generation to generation. At this time, This passenger coach being upgraded to reach the speed more than 120 Km/h and keep the ride quality and ride comfort index and called as stainless steel new generation (SS-NG) passenger coach. To reach the target one of the method is re-design the structure of bogie. The purpose of this research is to analyzing design of the SS-NG bogie, on SS-NG passenger coach using multibody dynamic simulation to studying rolling stock dynamic and compare it with existence bogie dynamic of SS-2018 passenger coach. The result of the simulation show the SS-NG bogie design give vertical and lateral ride comfort index appropriate to Sperling comfort index on center of carbody, center of front and rear bogie while operating at 240 Km/h.